Unpacking Meaningful Grammar Feedback: An Analysis of EFL Student Teachers’ Feedback Preferences and Learning Moments - Michel Cabot (Journal of Linguistics and Language Teaching)
Writing research has acknowledged the value of formative grammar feedback in English-as-a-foreign-language teacher writing education. Yet we know little about perceptions of the understanding and use of such meaningful feedback. To fill this research gap, two pilot interviews, ten semi-structured and four member-check interviews were carried out with twelve student teachers in Western Norway. To unpack feedback perceptions, these student teachers used two different essays as prompts (the first with written and oral feedback, the second without any feedback). The findings revealed that student teachers favoured feedback that pushed them cognitively and combined different feedback modes and types. Moreover, they commented positively on repetitive feedback with a high focus on accuracy. Student teachers’ awareness and the concreteness of the feedback given played important roles in the perception of learning moments. To discuss the findings, ecological-agentic theories were integrated with linguo-didactic theories. This study may inspire all those instructors who wish to develop their feedback practices.